2018
DOI: 10.1016/j.neubiorev.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

How do hypothalamic nonapeptides shape youth’s sociality? A systematic review on oxytocin, vasopressin and human socio-emotional development

Abstract: The hypothalamic nonapeptides oxytocin and vasopressin are important modulators of socio-affective behaviours in a wide variety of animal species, including humans. Nevertheless, there is little research addressing their possible roles on socio-affective dimensions of human behaviour across development, during which considerable behavioural and physiological change occurs. Questions still remain about the extent to which findings from adults may directly apply to earlier phases of human development. In this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 144 publications
(116 reference statements)
1
45
1
2
Order By: Relevance
“…However, the cortisol concentration after the PC (mean ± SEM = 0.18 ± 0.03 µg/dL) was higher compared to the NC (mean ± SEM = 0.14 ± 0.02), maybe due to the positive arousal [63]. The comparison with a negative, but static and unstressful, situation prevented possible bias due to the endogenous release of oxytocin in response to distress, as reported in humans [35][36][37][38][39], or due to locomotory activation [26]. In contrast to the studies mentioned above, we hypothesize that a decrease in salivary OXT could be correlated with a negative emotional impact.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, the cortisol concentration after the PC (mean ± SEM = 0.18 ± 0.03 µg/dL) was higher compared to the NC (mean ± SEM = 0.14 ± 0.02), maybe due to the positive arousal [63]. The comparison with a negative, but static and unstressful, situation prevented possible bias due to the endogenous release of oxytocin in response to distress, as reported in humans [35][36][37][38][39], or due to locomotory activation [26]. In contrast to the studies mentioned above, we hypothesize that a decrease in salivary OXT could be correlated with a negative emotional impact.…”
Section: Discussionmentioning
confidence: 79%
“…Another study in humans found that higher blood OXT levels after a stressful interpersonal task were associated with more anxiety, suggesting that oxytocin could be a marker of distress [38]. Furthermore, in humans oxytocin levels seem to be positively correlated with increased maternal separation distress in children [39].…”
Section: Introductionmentioning
confidence: 98%
“…This tool was first piloted in a subset of 10 references (LN, SM), and adjustments were made as necessary. Following the procedure adopted by other authors [33,34], we decided to use a customised appraisal tool to make sure we could capture specific aspects of the methodologies used in this field that, while important, could not be easily captured by a general-purpose instrument. For our purposes, we considered that aspects related with testing of causality and psychometric qualities of the measures used were important, but we could not find any existing measure specifically accounting for these two dimensions together.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…However, we found an association between carrying the A allele of rs4869317 and the increased eating disorders psychopathology level in the HCs group. In the context of theory concerning the potential role of LNPEP in social cognition and behaviour (see Torres, Martins, Santos, Prata, & Veríssimo, ; Zhang et al, ) and in the context of findings that these difficulties may be a characteristic for individuals with AN (Ambwani et al, ), the obtained result may have implications for the design of future studies investigating the role of the oxytocinergic system genes in developing eating disorders. To our knowledge, this is the first study in which the association between the level of eating disorders symptoms and carrying a specific allele of the LNPEP rs4869317 was found in healthy participants.…”
Section: Discussionmentioning
confidence: 88%